2019
DOI: 10.1002/ana.25486
|View full text |Cite
|
Sign up to set email alerts
|

TMEM106B Effect on cognition in Parkinson disease and frontotemporal dementia

Abstract: Objective: Common variants near TMEM106B associate with risk of developing frontotemporal dementia (FTD). Emerging evidence suggests a role for TMEM106B in neurodegenerative processes beyond FTD. We evaluate the effect of TMEM106B genotype on cognitive decline across multiple neurogenerative diseases. Methods: We longitudinally followed 870 subjects with diagnoses of Parkinson disease (PD; n = 179), FTD (n = 179), Alzheimer disease (AD; n = 300), memory-predominant mild cognitive impairment (MCI; n = 75), or n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 36 publications
2
52
0
Order By: Relevance
“…Genetic variants in TMEM106B have been linked with differential aging and various neurodegenerative diseases, including frontotemporal lobar degeneration (FTLD), limbic-predominant age-related TDP-43 encephalopathy (LATE), and Parkinson's disease (Nelson et al, 2019;Tropea et al, 2019;van der Zee et al, 2011). The precise molecular function of TMEM106B is, however, still enigmatic.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic variants in TMEM106B have been linked with differential aging and various neurodegenerative diseases, including frontotemporal lobar degeneration (FTLD), limbic-predominant age-related TDP-43 encephalopathy (LATE), and Parkinson's disease (Nelson et al, 2019;Tropea et al, 2019;van der Zee et al, 2011). The precise molecular function of TMEM106B is, however, still enigmatic.…”
Section: Introductionmentioning
confidence: 99%
“…These two genes were also found to be associated with TDP‐43 proteinopathy and coordinate with each other to regulate gene expression in a genome‐wide transcription study (Yang et al , ). Furthermore, GRN and/or TMEM106B polymorphisms are associated with FTLD caused by C9ORF72 mutations (van Blitterswijk et al , ; Deming & Cruchaga, ; Gallagher et al , ; Lattante et al , ), cognitive impairment in amyotrophic lateral sclerosis (ALS) (Vass et al , ) and Parkinson's disease (PD) (Baizabal‐Carvallo & Jankovic, ; Tropea et al , ), and pathological presentation of Alzheimer's disease (AD) (Lee et al , ; Rutherford et al , ; Kamalainen et al , ; Perry et al , ; Sheng et al , ; Xu et al , ). Thus, it is critical to understand the functions of GRN and TMEM106B and how they genetically interact to affect neurodegeneration.…”
Section: Introductionmentioning
confidence: 99%
“…A sex-specific analysis in UK Biobank further indicated that rs1990622 T allele only contributed to increased AD risk in females, but not in males (Table 2 ). Tropea and colleagues have also evaluated the association of rs1990622 variant with AD using 300 AD cases and 137 neurologically normal control subjects [ 7 ]. However, Tropea and colleagues did not identify any significant association of rs1990622 with AD [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, Yang and colleagues did not directly evaluate the association between rs1990622 variant and AD risk. Until now, it remains unclear whether rs1990622 variant is associated with AD risk, although a lack of significant association between rs1990622 variant and AD risk [ 7 ]. We think that this may be caused by inadequate sample sizes (300 AD cases and 137 controls) [ 7 ], and large-scale samples are needed.…”
Section: Introductionmentioning
confidence: 99%